IMPLEMENTASI KURIKULUM 2013 PENDIDIKAN ANAK USIA DINI - Rahmawati, Yana; Ismail, Yusuf; Anggraeni, Dewi (TARBAWY : Indonesian Journal of Islamic Education, 2019)
Abstract. This research aims to analyze the implementation of the curriculum of 2013 early childhood education (PAUD) in Islamic kindergarten Istana Dhuafa. In the implementation of this early childhood education, the curriculum of 2013 PAUD has a very important role as media to achieve educational objectives. But, in itâ€™s implementation, it still has many obstacles. Scientific approach is used in the implementation of the curriculum of 2013 PAUD. Scientific approach is a process of instruction designed in such a way that student actively construct the competence of attitude, knowledge, and skills through observing, asking, gathering information, thinking, and communicating. This research uses a qualitative approach. Data collection technique is conducted through observation, interview, and documentation. This research produces some important things about the implementation of scientific approach.Abstrak. Penelitian ini bertujuan untuk menganalisis implementasi Kurikulum 2013 Pendidikan Anak Usia Dini di TK Islam Istana Dhuafa. Dalam pelaksanaan pendidikan usia dini, Kurikulum 2013 PAUD berperan sangat penting sebagai alat untuk mencapai tujuan pendidikan. Namun, dalam pelaksanaannya masih mengalami berbagai kendala. Pendekatan saintifik digunakan dalam pelaksanaan Kurikulum 2013 PAUD. Pendekatan saintifik merupakan proses pembelajaran yang dirancang sedemikian rupa agar peserta didik secara aktif mengkonstruksi kompetensi sikap, pengetahuan, dan keterampilan melalui tahapan mengamati, menanya, mengumpulkan informasi, menalar, danÂ  mengomunikasikan. Pendekatan dalam penelitian ini menggunakan pendekatan kualitatif. Teknik pengumpulan data dengan cara observasi, wawancara, dan dokumentasi. Penelitian ini menghasilkan beberapa hal penting mengenai implementasi pendekatan saintifik.